Library youth outreach 26 ways to connect with children, young adults and their families - Harrod, Kerol 1972-; Smallwood, Carol 1939- (Jefferson, North Carolina McFarland & Company, Inc., Publishers, 2014)
"The outreach methods detailed by the authors of this book range from simple actions to detailed processes. Each of the 26 chapters provides helpful information for both those new to library outreach and those with years of experience"-- Provided by publisher.
Creative community connections / Gloria Adams -- Hospital storytelling outreach / André R. Powe -- Rooted in the community : small and rural library outreach / Michelle A. McIntyre and Melanie L. Ramsey -- Youth contests as outreach / Natalie Houston -- Annual programs for youth and community / Ann McDue -- Team outreach : librarians pairing up / Shawn D. Walsh and Melanie A. Lyttle -- It takes a village : a public and school library collaborate / Annie Miller -- Reaching kids who are experiencing homelessness / Vikki C. Terrile -- Booktalking for incarcerated teens : scalable, sustainable success from the Hennepin County Home School / Sara Zettervall and Amy Mars -- Youth focus groups : finding out what patrons really want / Brittany Nethers -- Outreach to Spanish-speaking families / Sarah Kaufman -- Reaching out to LGBTQ youth / Jamie Campbell Naidoo -- Early literacy outreach for teen parents / Corinne Sanchez and Xelena González -- Using (free) technology to reach out ... and bring in! / Amanda Nichols Hess -- Creating and running a digital bookmaking fair for school or public libraries / Stacy Creel -- Preschool outreach : small public library programs / Rebecca D. Richardson -- Taking your show on the road : STEM and early literacy storytime outreach / Josie B. Hanneman -- After-school storytimes : activities for elementary school outreach / Krissy Wick -- Traveling summer reading show / Carol H. Waxman and Susan M. Hansen -- Overnight at the library / Tami Morehart -- Art outreach : a library success story / Mary Lou Carolan -- Promoting the library and summer reading program : grabbing the attention of middle school students / Stefanie Blankenship -- Contests and after-school activities for middle school / Leigh A. Woznick -- Turntables and tater tots : lunchroom outreach that works / Leah Durand, Abigail Harwood, and Joseph Wilk -- Outreach outcome : I'm going to the library after school! / Joanna Nelson and Kaitlin Hoke -- Teen volunteers and children's programs : two for one programming / Sharon Colvin.
Includes bibliographical references and index.
Keywords: Library outreach programs -- United States; Libraries and teenagers -- United States; Libraries and community -- United States; Libraries and minorities -- United States; Children's libraries -- Activity programs -- United States; Young adults' libraries -- Activity programs -- United States; School libraries -- Activity programs -- United States; Library cooperation -- United States